Effect of MGO immersion time on dielectric layer properties of ZNO/MGO films / Mohammad Syafiq 'Afif Mohammad Rashidi - Mohammad Rashidi, Mohammad Syafiq 'Afif (2013)
This research work, focuses on the deposition of multilayer ZnO/MgO using immersion method deposited at different immersion time. The multilayer were deposited at 2, 4, 6, and 8 hours immersion time. The resistivity values obtained were varied in the range of 12.5 to 20.0 kΩ.cm which is due to the changes in carrier mobility and scattering. It was also found that, the leakage current, J was below than 10-8 A.cm-2 which is suitable for dielectrics. Some surface modification were observed as the immersion time increased from 2 to 8 hours which also reflect to the variation in resistivity, leakage current and k values obtained. The formation of flakes like structure was observed for multilayer films with 4 hours immersion time which leads to the enhancement in k value at high frequency region.